Victoria & Abdul : The True Story of the Queen's Closest Confidant - Basu, Shrabani (New Delhi, India Rupa Press, 2011)
The tall handsome Abdul Karim was just twenty-four when he arrived in England from Agra to wait at tables during Queen Victoria s Golden Jubilee. An assistant clerk at Agra Central Jail, he suddenly found himself a personal attendant to the Empress of India herself. Within a year, he was established as a powerful figure at court, becoming the queen s teacher, or Munshi, and instructing her in Urdu and Indian affairs. Devastated by the death of John Brown, her Scottish gillie, the queen had at last found his replacement.
Include Epilogue, Notes, Bibliography and Index
Keywords: Great Britain -- Courts and courtiers -- Favorites, Royal